Prognostic Discussions in Advanced Cancer: A Qualitative Thematic Analysis of Patients' and Caregivers' Experiences in a Tertiary Cancer Center in India - Tiwari, Avinash; Ghoshal, Arunangshu; Deodhar, Jayita; Muckaden, MaryAnn (Indian Journal of Medical and Paediatric Oncology, 2024)
Introduction Advanced cancer poses unique difficulties for patients, caregivers, and health care providers. Prognostic discussions are pivotal in shaping care decisions during this stage. These conversations involve health care professionals conveying disease progression, expected outcomes, and estimated life expectancy. Research consistently underscores the pivotal role of prognostic discussions in advanced cancer care, and most existing research stems from developed countries, necessitating the exploration of experiences within the Indian context.Objective The aim of this study is to identify the themes and patterns that emerge from the narratives of patients and caregivers surrounding prognostic discussions.Materials and Methods Using a qualitative methodology, participants were drawn from the palliative care clinic via a purposive sampling in this prospective qualitative study. Semi-structured interviews were conducted, and thematic analysis was employed to understand patient and caregiver experiences. Ethical considerations were adhered to throughout, obtaining informed consent and ensuring anonymity.Results Findings from 21 participants revealed five themes shaping prognostic discussions: perception and understanding of prognostic information, emotional impact, decision-making and treatment preferences, communication with providers, and cultural and religious influences. Patients struggled to comprehend complex medical terms, while caregivers played essential roles in aiding understanding. Both groups grappled with intense emotions upon learning of limited life expectancy, impacting decision-making. Effective communication and involvement of caregivers in discussions were pivotal, and cultural and religious beliefs shaped the perspectives on death.Conclusion This study emphasizes the intricate emotional landscape of patients and caregivers during advanced cancer prognostic discussions. It highlights the need for health care providers to undergo specialized communication training, prioritize shared decision-making, and respect cultural contexts. However, the study's limitations warrant future research for broader generalizability and long-term impact assessment.
Keywords: caregivers; palliative care; prognosis; prospective studies; communication; perception